Flouting Grice’s Maxim in Jumanji: The Next Level - Vahini, Putu Prasanthi; Budiarsa, Made; Netra, I Made (Udayana Journal of Social Sciences and Humanities, 2022)
The title of this study is Flouting Grice Maxim in Jumanji: The Next Level. This study aims to analyze the types of maxim flouting in the film and analyze the reasons for the flout. Data obtained from the film Jumanji: The Next Level, directed by Jake Kasdan. The data were obtained from the film Jumanji: The Next Level using the documentation method and note-taking technique. Data were analyzed using descriptive qualitative methods. This study uses the theory of Grice (1975) cooperative principle. The result showed that the maxim that mostly flouted is the maxim of relation.